Marble Corporation of the Philippines a production and operations management study - Buan, Melanie C.; Maramba, Amyzola, N.; Triunfante, Anna Marie R. (Diliman, Quezon City College of Engineering, 1999)
The Marble Corporation of the Philippines (MACOP) started as a small family-owned industry in 1978 under the name Milano Marble. Currently there are three buildings in the plant site. One of the buildings is allotted for the production of marble tiles for export. The other two buildings house the production of marble slabs and tiles that would be sold in the local market. The study group identified lack of storage space, overproduction and plant layout as the main problem areas. The company is faced with an overproduction and plant layout as the main problem areas. The company is faced with an overproduction problem because it is unable to determine the production quantity that will meet the demand for their product. The company does not use forecasting techniques to predict future demands for their product, thus it is unable to set a level at which it is to produce. The study group proposes that forecasting techniques be used by the company. From the forecasted value, the optimal order quantity and reorder point is also determined. The company processes marble blocks using similar machines, thus the study group suggests that similar machines be grouped together. Since the material handling cost is based on the distance traveled and the production volume, the proposed layout will reduce this cost, increase the current storage space, and improve flow of material. Implementing the recommendations will reduce the total annual cost of the company by 67.36%. The study group proposed that the production days be reduced to 8.125 days per month for the export line. This translates to 2 production days a week. The implementation of this proposal will leave the company with 3 free days a week. This can be utilized in the production of tiles for the local market. The study group suggests that the workforce be reduced.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: Marble Corporation of the Philippines; Marble industry and trade; Production engineering